Experimental investigation of vibration chatter in micromilling with minimum quantity lubrication: Analysis of signal-to-noise ratio and variance - Mohammad Yeakub, Ali; Muhammad Shaffiq, Hussin; Al-Hazza, Muataz Hazza; Rahman, Md Mustafizur; Singh, Ramesh; Abdul Md, Mazid (Taylor's University, 2024)
Application of minimum quantity lubrication (MQL) is found to increase tool life by reducing temperature generated at the cutting zone. However, uncontrolled vibration, known as chatter, remains as a critical issue in micro milling using MQL. Hence, researchers are looking for an imminent tool based micromilling process to improve tool life, machined surface quality and accuracy. This paper presents the ANOVA approach to analyse the synergistic effect of MQL and chatter in tool based micromilling. DT-110 (Mikrotools Inc, Singapore), a highprecision CNC micromilling machine, was used to produce microchannels on copper workpiece using 500 µm diameter end milling tools. The machining process was lubricated using MQL system (Bluebe FK) with a biodegradable vegetable-based oil. Microchannels were machined following Taguchi Orthogonal Array (L16) design comprising micromilling and MQL parameters. Then amplitude of chatter and spindle speed frequency were analysed as chatter ratio. The research showed that the nozzle direction has the highest significance for chatter. The spindle speed has the lowest influence compared to other parameters such as nozzle pressure, MQL flow rate and depth of cut. Several interactions between parameters were also found to be significant. The interaction between MQL flow rate and nozzle direction was found to be most significant. Finally, this experimental investigation found 3.75 ml/hr MQL flow rate, 270° flow direction, 0.275 MPa nozzle pressure, 50 µm depth of cut and 50000 rpm spindle speed as optimum.